Systematic Review of the Effects of Early Family/Parent Training Programs on Antisocial Behavior and Delinquency, 1976-2007 - Piquero, Alex ([Verlag nicht ermittelbar], 2012)
The purpose of this review was to assess the available research evidence on the effects of early family/parent training on child behavior problems including antisocial behavior and delinquency and to investigate in which settings and under what conditions it is most effective. Researchers used the following 7 search strategies to identify 55 studies meeting the inclusion criteria for this review: performed a keyword search on an array of online abstact databases; reviewed the bibliographies of previous reviews of early family/parent training programs; performed forward searches for works that have cited seminal studies in this area; performed hand searches of leading journals in the field; searched the publications of several research and professional agencies; contacted scholars in various disciplines who were knowledgeable in the specific area of early family/parent training; and consulted with an information specialists at the outset of the review and at points along the way in order to ensure that the appropriate search strategies were used. Both published and unpublished reports were considered in the searches. Searches were international in scope. All eligible studies were coded on a variety of criteria including: reference information, nature and description of selection of sample, outcomes, etc., nature and description of control group, methodological type, a description of the family/parent intervention, reports of statistical significance (if any), effect size/power (if any), and the conclusions drawn by the authors.